The Reflux Symptom Index (RSI) as a Diagnostic Tool for Laryngopharyngeal Reflux (LPR) - Athanasia Printza; Athanassios Kyrgidis (Archives of The Medicine and Case Reports, 2022)
Laryngopharyngeal reflux (LPR) is the backflow of gastric contents into the laryngopharynx, where the gastric contents will come into contact with the upper aerodigestive tract tissue. These clinical entities are known to profoundly affect the patient's quality of life, altering sleep and daily activities and reducing the effectiveness of the speaker's communicator. The Reflux Symptom Index (RSI) was developed in 2001 for the purpose of diagnosing laryngopharyngeal reflux. The RSI is a validated nine-item instrument that focuses on LPR symptoms, including hoarseness, frequent clearing of the throat, globus, cough, and dysphagia. A score of more than 13 was considered abnormal and reflected LPR, and improvement at an RSI > 5 points was considered clinically significant.